Septic Lateral Sinus Thrombosis: Sinus Exploration Is Unnecessary. (12th January 2016) - Singh, Gautam Bir; Arora, Rubeena; Garg, Sunil; Kumar, Deepak; Ranjan, Shruti
Abstract : The algorithm of treatment of septic lateral sinus thrombosis (SLST) has undergone a paradigm shift with the understanding of the natural history of sigmoid sinus thrombosis. Thus, the recent medical literature promulgates the management of these cases with no sinus exploration. However, in view of marked paucity of literature on the cited subject, not much is known about this form of treatment. We present our experience of treating two paediatric cases of SLST with mastoid surgery and no sinus exploration: both cases had excellent recovery. Finally, conclusions are drawn in light of contemporary literature on this subject.